KAWASAN WISATA TEPIAN SUNGAI BUAYA SEBAGAI FASILITAS REKREATIF EDUKATIF KABUPATEN BULUNGAN KALIMANTAN UTARA - Irfan Hafidz Assidiq; Ira Mentayani (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
According to the Provincial Government of North Kalimantan, it has an area of 13,182 km² with a population of the entire district of 701,814 people (results of the 2020 Indonesian population census). The Crocodile Riverside Tourism Area located in downtown Tanjung Selor Hilir, North Kalimantan. It is planned as a place to visit tourism and take advantage of the potential of fishing villages by improving fishing facilities. The Crocodile Riverside Tourism Area is designed to apply a RecreativeEducational approach. Contextual Architecture is defined as the process of designing a building, which takes into account the existing site conditions. The purpose of the Contemporary Architecture Design for the Tanjung Selor Hilir 2 Riverside Crocodile Tourism Area project in North Kalimantan is planned to apply the Contextual Architecture Approach.